Interlayer Modification of West Java Natural Bentonite as Hazardous Dye Rhodamine B Adsorption - Satria Jaya Priatna; Yusuf Mathiinul Hakim; Sahrul Wibyan; Siti Sailah; Risfidian Mohadi (Science and Technology Indonesia, 2023)
This work reports the modification of West Java natural bentonite as an effective adsorbent for rhodamine B dye. The modification was finished by sodium intercalation at room temperature to get low-energy preparation. Characterization of bentonite-modified adsorbent was used SEM, XRD, FTIR, and BET analysis. The material pore size and surface area were increased by 0.303 nm and 178.710 m2/g on Na-bentonite. The adsorption mechanism conformed well with the Freundlich isotherm model and pseudo-second-order kinetics equations. The adsorption process by thermodynamic analysis was endothermic and advantageous. Under the optimum condition of pH 6 (confirmed by pHpzc), initial dye concentration of 125 mg/L, and the adsorbent dosage of 0.09 g for 65 minutes, the Na-bentonite has a larger adsorption capacity (Qm) of 142.86 mg/g, while the different adsorbent dosages of 0.11 g for 75 minutes, the adsorption capacity of natural bentonite (Qm) reaches 140.85 mg/g. This work provides a method for establishing a low-energy preparation adsorbent of bentonite-based on Na intercalant as a low-cost and valuable adsorbent for waste dye removal.